Review of the empirical equations for predicting the shear strength of unsaturated soils - Garven, Elizabeth A (University of Ottawa (Canada), 2009)
Shear strength is a key engineering property required in the design of several geotechnical structures that include earth dams, pavements, slopes, retaining walls and foundations. In many situations these structures are constructed with unsaturated soils or in soils that are placed in a state of unsaturated condition. The designs of these structures are based on conventional soil mechanics assuming that the soil is in a state saturated condition resulting in conservative estimations. Several experimental techniques are presently available and more are evolving for determining the shear strength of unsaturated soils in the laboratory environment in this emerging research area that is of significant practical interest. However, these experimental techniques are expensive, time consuming and need elaborate testing equipment. In addition, qualified and trained personnel are required for reliably determining the shear strength behaviour of unsaturated soils. Due to these reasons, the focus of investigations in recent years has been directed towards predicting the shear strength of unsaturated soils. There are several techniques that include semi-empirical, empirical and mathematical fitting relationships that can be used in the prediction or estimation of the variation of shear strength of unsaturated soils with respect to suction. Such techniques are encouraging towards extending the mechanics of unsaturated soils into engineering practice. In spite of recent advances in the field of unsaturated soils, few practitioners have background with respect to the shear strength behaviour and the mechanics of unsaturated soils. This thesis provides a historical background of the development of concepts related to our present understanding of the shear strength behaviour of unsaturated soils. The techniques of interpreting the shear strength behaviour proposed by various investigators are also summarized. The details presented in the thesis also include the state-of-the-art testing procedures for determining the shear strength behaviour. In addition, a wealth of 130 soils data published in the literature from various conferences and journals from all over the world are summarized. There are twenty-five different equations that are available in the literature to predict the variation of shear strength with respect to suction using different techniques. All these techniques are summarized providing details of the philosophies used in the development of these equations. Thirteen of the above equations use the soil-water characteristic curve (SWCC) and the saturated shear strength parameters (c' and &phis;') for predicting the shear strength of unsaturated soils. Other techniques that include mathematical fitting models and empirical relationships for estimating the shear strength of unsaturated soils are also summarized. Seven prediction equations commonly used in the literature are chosen from the available 25 equations in the literature to predict the variation of shear strength with respect to suction using 130 data sets of published experimental results from the literature. A quantitative assessment method is used in comparing the predicted and measured shear strength results of the 130 sets. Each of the seven prediction equations is able to successfully predict the variation of shear strength with respect to suction for some of the soils; however, approximately 8% of the soils were not able to be successfully predicted by any of the 7 equations. The shear strength behaviour of unsaturated soils if a complex relationship which is dependent on many factors including stress history, density, soil structure or fabric, water content, volume change behaviour during shearing state and testing techniques. For example, recent developments in shear strength testing techniques show that previously measured water content in samples may not be representative of the actual water content due to diffused air, condensation and evaporation in the system. In other words, the simple prediction procedures that are available in the literature are not capable of taking into account many complex parameters that influence the shear strength behaviour of unsaturated soils. Therefore, the available techniques or procedures have to be used in practice with engineering judgment while predicting the shear strength of unsaturated soils. Some guidelines and recommendations are provided with respect to the available prediction procedures such that practicing engineers and other investigators can use them understanding the strengths and weaknesses. Finally, the research work summarized in this thesis is also useful for other investigators to undertake future work in the area of shear strength of unsaturated soils to better understand its behaviour.
Keywords: Engineering, Civil.